Effect of corrugation angle on the hydrodynamic behaviour of power-law fluids during a flow in plate heat exchangers - Fernandes, Carla S. (2010)
In this study, CFD calculations were made in order to analyze the hydrodynamic behaviour of a power-law fluid in the channels of plate heat exchangers with corrugation angles of 30º and 60º during a non-isothermal flow. For the observed laminar flow, the numerical results show that a typical velocity profile in the 3D channel of the plate heat exchanger with corrugation angle 30º assumes an approximate parabolic shape and that for a corrugation angle of 60º the profile have a irregular core. Simulations considering and discarding the influence of temperature on the non-Newtonian fluid viscosity were performed for the two geometries and the impact of these variations on the relations between fanning friction factors and Reynolds number was analyzed as well as on the ratio between wall and bulk shear rate.